Influence of Nigerian Movies on the Cultural Values of Youths in Delta State, Nigeria - IVWIGHREN, Hannah Emuobosa; URHIBO, Bridget Onajite; UWAYAH, Lydia I. (Management Research and Behavior Journal, 2024)
This study looks at how movies affect Nigerian youth culture, especially for the second generation of millennials”those born between 1995 and 2004. Films have had a significant influence since the late 1920s. In the 1950s, as this medium became more and more popular, worries about possible risks also increased, particularly with regard to young audiences. This study evaluates how important a role film has played in the development of Nigerian youth culture. It also looks at the differences between film and other mass media in terms of how much of an impact film has had on the country's youth culture. The survey method of data collecting and analysis is used in this study, which the cultivation theory of mass communication serves as the pivot. With the use of SPSS software, it also employs descriptive and inferential statistics for data analysis. According to the study, movies have a huge influence on young culture because they can emotionally connect with audiences and depict serious subjects in a way that is agreeable, relatable, and entertaining. Consequently, the study suggested that in order to fully utilize movies' potential as a tool for teaching young people moral principles, cooperation between the Nigerian government and the country's film industry should be established.